ORGANIZING GAMES FOR COGNITIVE DEVELOPMENT IN SCHOOL CHILDREN - Fozilova Odina Nabiyevna (Western European Studies, 2024)
This article examines the role of games in fostering cognitive development in school-aged children. By exploring various types of games and their impact on key cognitive skills such as memory, problem-solving, attention, and critical thinking, the study highlights the importance of structured play in educational settings. The article reviews the current literature on game-based learning, discusses effective methods for implementing games in the classroom, and presents results from practical applications. Findings suggest that games significantly enhance cognitive growth and support the holistic development of children
Keywords: Cognitive development; school children; educational games